Foods, nutrients and hip fracture risk: A prospective study of middle-aged women. Issue 12 (December 2022) - Webster, James; Greenwood, Darren C.; Cade, Janet E.
Summary: Background and aims: Hip fracture affects 1.6 million people globally each year, and increases morbidity and mortality. There is potential for risk reduction through diet modification, but prospective evidence for associations between intake of several foods and nutrients and hip fracture risk is limited. This study aimed to investigate associations between food and nutrient intakes and hip fracture risk in the UK Women's Cohort Study, and to determine the role of body mass index (BMI) as a potential effect modifier. Methods: Dietary, lifestyle, anthropometric, and socio-economic information of UK women, ages 35–69 years, were collected in a survey at recruitment (1995–1998), and included a validated 217-item food frequency questionnaire. Hip fracture cases were identified by linking participant data at recruitment with their Hospital Episode Statistics (HES) up to March 2019. Cox regression models were used to estimate associations between standard portions of food and nutrient intakes and hip fracture risk over a median follow-up time of 22.3 years. Results: Among 26, 318 women linked to HES data (556, 331 person-years), 822 hip fracture cases were identified. After adjustment for confounders, every additional cup of tea or coffee per day was associated with a 4% lower risk of hip fracture (HR (95% CI): 0.96 (0.92, 1.00)). A 25 g/day increment of dietary protein intake was also associated with a 14% lower risk of hip fracture (0.86 (0.73, 1.00)). In subgroup analyses, BMI modified linear associations between dietary intakes of protein, calcium, total dairy, milk, and tea and hip fracture risk (pinteraction  = 0.02, 0.002, 0.003, 0.001, and 0.003, respectively); these foods and nutrients were associated with a reduced risk of hip fracture in underweight but not healthy or overweight participants. In particular, risk of hip fracture in underweight participants (28 cases, 545 participants) was 45% lower for every 25 g/day protein consumed (0.55 (0.38, 0.78)). Conclusions: This is the first prospective cohort study internationally of multiple food and nutrient intakes in relation to hip fracture risk by BMI using linkage to hospital records. Results suggest that the potential roles of some foods and nutrients in hip fracture prevention, particularly protein, tea and coffee in underweight women, merit confirmation. Protocol registration: Clinicaltrials.gov NCT05081466.